The effect oF Ca and thixoforming process on hardness and microstructure oF Mg–Al–Zn alloys - Adi Ganda Putra; Azwar Manaf; Djoko Hadi Prajitno (Journal of Materials Research and Technology, 2022)
Magnesium-based materials are lightweight materials that are 60% lighter in weight than steel, but the strength of these materials must be increased. This study was conducted on the effects of various Ca addition in (90-x)Mg–9Al–Zn-xCa (x = 0.0, 1.0, 1.5 and 2.0 wt.%) alloy samples made by casting and thixoforming processes. The alloy with x = 1.0 wt.% Ca yielded the microstructure consisting of α-Mg and β-Mg17Al12 with the mass fraction 83.1% and 16.9% respectively. The mass fraction α-Mg decreased to 50.3% and that of after β-Mg17Al12 increased to 49.7% after the thixoforming process. The increase in the mass fraction of the β-Mg17Al12 phase was caused by the heating process and the suppression force and the occurrence of grain refinement caused by the addition of Ca, which played a role in increasing hardness. The added Ca is an element that supports grain refinement and the formation of Al2Ca intermetallic compounds and reduces the growth of the β-Mg17Al12 phase. The hardness of the as-cast sample was originally 68 HB and increased to 82 HB.